Análise do ambiente do Pokémon Go considerando a arquitetura da informação pervasiva - Bezerra, Irvin Soares (2017)
In Information Science research related to the use of information has been developed, with influence of information technology and telecommunications. Its development was more accelerated in the post-industrial period when society began to produce a large amount of information. In the 21st century, access to information through the use of the Internet with smartphones has become something within reach of the population, providing an increase in communication. The objective of this work was to analyze the Pokémon GO application, considering the Architecture of Pervasive Information, when the motivation of the use of this theme was the recent launch of applications for smartphones that use pervasive environments, highlighting the game that became a huge Success of downloads and brought a great innovation in the way of play. For the accomplishment of this research, the participant research methodology was adopted, in which the user-researcher interacts directly with the searched object. The collected data were analyzed in a qualitative way. Using the game environment and evaluating the pervasive interaction presented at the threshold between the physical and digital environment, the heuristics described by Resmini and Rosati (2011) were considered. In the use of the game were explored the physical environments present in the city of João Pessoa, in addition to the moments of interaction. In the results the adherence to the proposed heuristics was discussed and these were punctuated as Present, Partially Present and Not Present. Finally, the data were analyzed suggesting improvements both for the game, considering the Pervasive Information Architecture, and for the environment itself.